Nitrogen Application and Oat's Genotypes Influence Nutritional Aspects of Oats (Avena sativa L.) Grains at Milky and Mature Stage of Development - Kaur, Gurjeet; Goyal, Meenakshi (Indian Journal of Animal Nutrition, 2017)
The objective of this study was to investigate effect of applied nitrogen on fodder yield and nutritional composition of oats seed comprising four genotypes (OL-9, Kent, OL-10 and OL-125). Experiment consisted of four nitrogen treatments i.e. 0, 50, 7 It was found that N application increased (P